Ustilago maydis produces itaconic acid via the unusual intermediate trans‐aconitate. Issue 1 (7th December 2015) - Geiser, Elena; Przybilla, Sandra K; Friedrich, Alexandra; Buckel, Wolfgang; Wierckx, Nick; Blank, Lars M; Bölker, Michael
Summary: Itaconic acid is an important biomass‐derived chemical building block but has also recently been identified as a metabolite produced in mammals, which has antimicrobial activity. The biosynthetic pathway of itaconic acid has been elucidated in the ascomycetous fungus A spergillus terreus and in human macrophages. In both organisms itaconic acid is generated by decarboxylation of the tricarboxylic acid (TCA) cycle intermediate cis ‐aconitate. Here, we show that the basidiomycetous fungus U stilago maydis uses an alternative pathway and produces itaconic acid via trans ‐aconitate, the thermodynamically favoured isomer of cis ‐aconitate. We have identified a gene cluster that contains all genes involved in itaconic acid formation. Trans ‐aconitate is generated from cis ‐aconitate by a cytosolic aconitate‐Δ‐isomerase (Adi1) that belongs to the PrpF family of proteins involved in bacterial propionate degradation. Decarboxylation of trans ‐aconitate is catalyzed by a novel enzyme, trans ‐aconitate decarboxylase (Tad1). Tad1 displays significant sequence similarity with bacterial 3‐carboxy‐ cis, cis ‐muconate lactonizing enzymes (CMLE). This suggests that U . maydis has evolved an alternative biosynthetic pathway for itaconate production using the toxic intermediate trans ‐aconitate. Overexpression of a pathway‐specific transcription factor (Ria1) or a mitochondrial tricarboxylic acid transporter (Mtt1) resulted in a twofold increase in itaconate yield. Therefore, our findings offer new strategies for biotechnological production of this valuable biomass‐derived chemical. Abstract : Itaconic acid is an important bio‐based chemical building block, which is currently produced by Aspergillus terreus via decarboxylation of cis ‐aconitate.Identification and characterization of responsible genes for itaconic acid biosynthesis in Ustilago maydis showed that this basidiomycetous fungus uses an alternative pathway and produces itaconic acid via the unusual intermediate trans ‐aconitate.Overexpression of pathway‐specific genes resulted in a significant increase in itaconate yield, thereby offering new strategies for biotechnological production of this valuable biomass‐derived platform chemical.